Implementation of Pancasila Ideology Learning to Prevent Student Radicalism in Elementary School Teacher Education Programs - Maksum, Hafidh; Muttaqien, Fauzan; Stanislaus, Surip; Surya, Muhamad Hendry; Fatmawati, Endang; Lawang, Karimuddin Abdullah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study analyzes strategies for implementing Pancasila values in the learning process aimed at shaping moderate, tolerant, and patriotic character among students of the Primary School Teacher Education (PGSD) Program at Universitas Serambi Mekkah. Employing a qualitative field research design, data were collected through classroom observations, in-depth interviews with lecturers and students, and documentation of instructional materials, including Semester Learning Plans (RPS), teaching resources, and academic activity records. Data analysis was conducted using descriptive qualitative techniques encompassing data reduction, data presentation, and conclusion drawing, and was reinforced by a review of relevant literature on radicalism, ideological education, and the internalization of Pancasila values in higher education. The findings reveal that the internalization of Pancasila values through contextual learning strategies, such as dialogical discussions, reflective learning, case-based instruction, the strengthening of ideological literacy, and lecturers’ exemplary conduct, contributes significantly to enhancing students’ awareness of diversity, religious moderation, and national unity. Students not only acquire cognitive understanding of Pancasila but also demonstrate the practical internalization of its values in their daily social interactions. This process strengthens students’ ideological resilience and reduces their susceptibility to radical narratives within the campus environment. The study concludes that learning Pancasila ideology plays a strategic role in preventing radicalism and serves as a fundamental pillar for reinforcing students’ national identity. These findings emphasize the importance of strengthening ideological education in a systematic and sustainable manner to foster a moderate, inclusive, and nationally oriented academic environment.